The Potential of Digitalisation and Social Dialogue in Ensuring Post-Pandemic Labour Market Sustainability: Priorities for Ukraine - Novikova, Olga; Pankova, Oksana; Chaliuk, Yuliia; Kasperovich, Oleksandr (Studies of Transition States and Societies, 2021)
The article substantiates promising areas of resource mobilisation to counter the negative effects of the COVID-19 pandemic оn the labour market, namely, through the involvement of the potential of digital, information and communication technologies and the introduction of innovative mechanisms into the system of social dialogue in the labour field at the national level. The conceptual basis of the research is the four-pillar policy framework for tackling the socio-economic impact of the COVID-19 crisis, developed by the International Labour Organization as a basic tool to address the risks and threats of the COVID-19 pandemic for global and national labour markets. This framework was used as a cross-cutting analytical scheme to analyse Ukrainian realities and further to structure the potential of digitalisation and social dialogue for overcoming the negative impact of the COVID-19 pandemic on the Ukrainian labour market and for further post-pandemic recovery.Based on the modern platform approach, the authors propose a social innovation – a 3-element model of socially responsible partnership (SRP Platform), which allows significantly updating (or even rebooting) the system of communication and interaction between the social dialogue participants in Ukraine using the potential of modern network, information and communication technologies. Implementating such a model will contribute to the renewal of the social dialogue system in Ukraine and, thus, further effective counteraction against the impact of the COVID-19 pandemic, ensuring the sustainable functioning of the Ukrainian labour market, and to the formation of an effective anti-pandemic state policy. Both the conceptual basis and general mechanism for implementing the SRP platform are (to a large extent) universal and can be adapted to renew social dialogue systems not only in Ukraine but also in other post-Soviet countries with a tripartite system.